An epithelial to mesenchymal transition programme does not usually drive the phenotype of invasive lobular carcinomas. Issue 4 (1st February 2016) - McCart Reed, Amy E; Kutasovic, Jamie R; Vargas, Ana C; Jayanthan, Janani; Al‐Murrani, Amel; Reid, Lynne E; Chambers, Rachael; Da Silva, Leonard; Melville, Lewis; Evans, Elizabeth; Porter, Alan; Papadimos, David; et al.
Abstract: Epithelial to mesenchymal transition (EMT) is a cellular phenotype switching phenomenon which occurs during normal development and is proposed to promote tumour cell invasive capabilities during tumour progression. Invasive lobular carcinoma (ILC) is a histological special type of breast cancer with a peculiar aetiology – the tumour cells display an invasive growth pattern, with detached, single cells or single files of cells, and a canonical feature is the loss of E‐cadherin expression. These characteristics are indicative of an EMT or at the very least that they represent some plasticity between phenotypes. While some gene expression profiling data support this view, the tumour cells remain epithelial and limited immunohistochemistry data suggest that EMT markers may not feature prominently in ILC. We assessed the expression of a panel of EMT markers (fibronectin, vimentin, N‐cadherin, smooth muscle actin, osteonectin, Snail, Twist) in 148 ILCs and performed a meta‐analysis of publically available molecular data from 154 ILCs. Three out of 148 (2%) ILCs demonstrated an early and coordinated alteration of multiple EMT markers (down‐regulation of E‐cadherin, nuclear TWIST, and up‐regulation of vimentin, osteonectin, and smooth muscle actin). However, the data overall do not support a role for EMT in defining the phenotypic peculiarities of the majority of ILCs. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.